MathOverflow is a question and answer site for professional mathematicians. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $M$ be a manifold and fix a Lagrangian $L\in C^\infty(T M )$. Let $x_1,\dots x_n$ be local coordinates for $M$ and equip the tangent bundle and cotangent bundle with standard coordinates $(x_1,\dots, x_n, v_1,\dots, v_n)$ and $(x_1,\dots, x_n,\xi_1,\dots, \xi_n)$ respectively. The Legendre transform associated to $L$ is $$\Phi_L: T M\to T^\ast M \ , \ (p,X_p)\mapsto \Phi_{L_p}(p,X_p):=(p,\frac{\partial L}{\partial v}(p,X_p))$$We also define the dual function associated to $L$ which is $$L^\ast:T^\ast M\to\mathbb{R} \, \ (p,\alpha_p)\mapsto \min \left\{\alpha_p(X_p)-L(p,X_p) \ , \ (p,X_p)\in T M\right\} $$ Under certain conditions on $L$, we get that $\Phi_L$ is a diffeomorphism with inverse $$\Phi_L^{-1}(p,\alpha_p) = (p,X_p) \text{ where $(p,X_p)$ minimizes } \alpha_p-L$$It can be shown that $$\Phi_L^{-1}=\Phi_{L^\ast}$$My question is about the following claim. $$\text{If } \Phi_L(p,X_p)=(p,\alpha_p)\text{ then } \frac{\partial L}{\partial x}(p,X_p)=-\frac{\partial L^\ast}{\partial x}(p,\alpha_p)$$ This is proved in Da Silva's book "Lectures on Symplectic Geometry" in the chapter on Hamiltonian mechanics. I do not understand her proof. Letting $H=L^\ast$, the definition of $H$ is $H(x_1,\dots x_n,\xi_1,\dots,\xi_n)=H(x,\xi)=\xi(x,W)-L(x,W)$ where $(x,W)=\Phi_L^{-1}(x,\xi)=\Phi_H(x,\xi)$ or equivalently $\xi=\Phi_L(W)$ so that $\xi$ is a function of the $x_i's$ and $v_i's$. She takes the total derivative of both sides of this equation with respect to $x$ to get $$\frac{\partial H}{\partial x}+\frac{\partial H}{\partial \xi}\frac{\partial \xi}{\partial x}=\frac{\partial\xi}{\partial x}v-\frac{\partial L}{\partial x}$$ The left hand side is just the chain rule, right? But how is the right hand side obtained? If $\xi$ is dependent on $x$ and $v$ then isn't $v$ dependent on $x$ and $\xi$? I believe that once we have this formula the hypothesis gives us the result as $\frac{\partial H}{\partial \xi_i}(p,\alpha_p)=v^i(p,W_p)$. If someone could walk me through this calculation it would be greatly appreciated, I have spent more time on this then I would like to admit.

share|cite|improve this question
The claim is fairly easy to prove when $M=\mathbb{R}$; maybe that case will help you sort things out. – Brendan Murphy Jun 29 '14 at 0:48
up vote 0 down vote accepted

I actually was interpreting what she was saying wrong. The coordinates $\xi$ on $T^\ast M$ are of the form $\xi=\Phi_L(x,v)$ so that $\xi_i=\frac{\partial L}{\partial v_i}$ and the Legendre transform is involutive so $\Phi_L^{-1}(\xi)=\Phi_{L^\ast}(\xi)=v$. This makes the computation fairly straightforward.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.